Politics and conflict in governance and planning Theory and practice - Eraydin, Ayda; Frey, Klaus (Routledge, 2019)
Politics and Conflict in Governance and Planning offers a critical evaluation of manifold ways in which the political dimension is reflected in contemporary planning and governance. While the theoretical debates on post-politics and the wider frame of post-foundational political theory provide substantive explanations for the crisis in planning and governance, still there is a need for a better understanding of how the political is manifested in the planning contents, shaped by institutional arrangements and played out in the planning processes. This book undertakes a reassessment of the changing role of the political in contemporary planning and governance. Employing a wide range of empirical research conducted in several regions of the world, it draws a more complex and heterogeneous picture of the context-specific depoliticisation and repoliticisation processes taking place in local and regional planning and governance. It shows not only the domination of market forces and the consequent suppression of the political but also how political conflicts and struggles are defined, tackled and transformed in view of the multifaceted rules and constraints recently imposed to local and regional planning.